Race, resources, and representation: Evidence from Brazilian politicians - Natália S. Bueno; Thad Dunning (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
What explains the persistence of racial or ethnic inequalities in political representation, in the absence of strongly politicized racial or ethnic cleavages? This paper uses new data to demonstrate a substantial racial gap between voters and politicians in Brazil. We show that this disparity is not plausibly due to racial preferences in the electorate - for instance, deference towards white candidates, or discrimination against non-whites. Nor do barriers to candidate entry or discrimination by party leaders likely explain the gap. Instead, we document the importance of persistent resource disparities between whites and non-whites - especially, differences in personal assets and in campaign contributions. Our findings show how the power of numerical racial minorities may persist in democracies, even in the absence of racialized politics, and highlight the role of investments by economic elites in a setting in which race and class substantially overlap.
Keywords: 330; descriptive representation; racial democracy; Brazil; experiments